A Coupled Approach to Simulate the Explosion Response of a Buried Structure in a Soil-Rock Layered Medium. Issue 3 (September 2013) - Feldgun, V.R.; Karinski, Y.S.; Yankelevsky, D.Z.
The paper presents an investigation on the response of a buried structure in a soft soil layer above a rock bed that is subjected to blast loading. A comprehensive approach to simulate the behavior of soft soil with a buried structure laying over a rock mass due to the dynamic (explosive) action in the rock mass is presented. The numerical algorithm was developed to simulate the shock wave propagation within the medium, considering both the bulk and deviatoric damage and taking into account the possible shear damage accumulation. It takes into account the contact conditions between the layers to simulate the shock wave transmission and the soil-structure interaction including their possible separation. The soil-lining interaction problem is solved by a combination of the variational-difference method (for the lining) and of the Godunov's method (for the soil). The coupling of these two approaches is performed by calculation of the contact stresses and velocities on the soil-lining boundary. Two types of the soil models were investigated – an ideal elastic plastic medium and an irreversible compressible medium with failure in bulk tension – and the results were compared with each other. The analysis of the free surface and interface velocities and displacements as well as the contact stresses and the damage at the media interface were carried out. The effects of the relative cover thickness on the interface and free surface behavior is studied. Analysis of the contact stresses at the soil-tunnel interface, was carried out. The effect of the charge location as well as the effect of the soil-rock interface on the tunnel's response was investigated.